Mathematicians. an outer view of the inner world (2009)
Mathematicians. An Outer View of the Inner WorldMariana CookPrinceton University Press, Princeton, 2009200 paginas. 92 fotografas. Indice de fotografas.Gran formato (30 x 26 cm.)